The Influence of Commitment and Organizational Culture to Licensing Services Performance in Licensing Integrated Services Agency (BPPT) Bekasi - Akbar, M. Firaldi; Rudito, Bambang (Journal of Business and Management, 2012)
Reforms that have been fought by the people of Indonesia have a common goal is the clean government, clean business, and clean environment. People have started to get bored with a bureaucratic culture that leads to acts of corruption. Difficulty getting permission to start a business for those who do not have the closeness with the government are real things that happen in every line of life. Thus the whole issue raises the question of how employee commitment in implementing an integrated licensing and how organizational culture that involves the Operator Licensing Agency and the Organization of the regional Integrated involved in the process of permit issuance.The method used is contributional research method, with linear regression statistical processing techniques. Samples to be used was 69 people, with the sampling technique used in this study was purposive sampling. Processing the data using multiple regression statistical calculations.Results of the study, there was a significant effect on Â the commitment and Cultural Organization to the employee performance Perizinan Integrated Services in Pelayanan Perizinan Terpadu in Â Badan Pelayanan Perizinan Terpadu (BPPT) Kota BekasiKeywords: Bureaucracy, commitment, culture, prformance, contributionÂ